Identification of Indicators and Components of Attentive Leadership among Educational Managers in Mazandaran Province - Salehi Bandebeni, Rasool; Taghvaee Yazdi, Maryam; Uosefi Saeedabadi, Reza (Assessment and Practice in Educational Sciences, 2025)
The present study aimed to identify the indicators and components of attentive leadership among educational managers in Mazandaran Province. This research is applied in terms of purpose and qualitative with an exploratory mixed-methods design in terms of data nature. Accordingly, in the qualitative phase, based on grounded theory, a descriptive–survey method was used to identify the indicators and components of attentive leadership among educational managers. The statistical population in the qualitative section included all experts, policymakers, managers, and academic planners, as well as officials from the Department of Education in Mazandaran Province. The sampling method in the qualitative phase was theoretical and purposive, aligned with the principle of theoretical saturation, and a total of 10 participants were selected as the sample. Data collection in the qualitative phase was conducted using semi-structured interviews. The validity and reliability of the data were confirmed. The findings revealed 14 components of attentive leadership, including: defining a strategic direction and future vision; strategic thinking and future foresight; maintaining flexibility and change management; developing human capital and organizational culture; emphasizing ethical values; eliminating distractions; demonstrating friendly and supportive behavior; behavioral flexibility of the leader; creating and sustaining positive working relationships; open communication and feedback reception; empathy and attention to individual needs; decision-making and problem-solving; analytical and critical thinking; and emotional and social intelligence among educational managers in Mazandaran Province.